The conspicuous postmetamorphic coloration of fire salamanders, but not their toxicity, is affected by larval background albedo. Issue 1 (6th February 2019) - Sanchez, Eugenia; Pröhl, Heike; Lüddecke, Tim; Schulz, Stefan; Steinfartz, Sebastian; Vences, Miguel
Abstract: Experimental work in the early 20th century showed that background albedo experienced by larvae of the fire salamander ( Salamandra salamandra ) induce a durable morphological modification of the postmetamorphic color pattern, which needed confirmation due to the controversies regarding Paul Kammerer's experiments. Such a carry‐over effect would be relevant as the black and yellow pattern of the alkaloid‐containing adult fire salamanders has been suggested to serve as an aposematic signal. Hence, we hypothesized that (a) adult coloration is conspicuous to potential predators under light conditions at night, given the nocturnal activity of this species, and (b) a condition affecting the salamander's coloration pattern would also affect its toxicity to maintain a quantitatively honest aposematic signal. To test the first hypothesis, we used spectrometry to model the vision of potential avian and snake predators and confirmed that fire salamander's black‐and‐yellow pattern is contrasting enough against the forest leaf litter to be considered conspicuous at night. To test the second hypothesis, we first confirmed the background carry‐over effect on black and yellow proportions in the dorsal skin of experimentally reared fire salamanders, using a rigorous experimental design. Then, we calculated the conspicuousness and determined the alkaloid profiles of these individuals. We did not find a correlation between conspicuousness and toxicity at the intrapopulation level. Moreover, there was no background carry‐over effect on the alkaloid profile. We discuss our results in a physiological, ecological, evolutionary, and historical context. Abstract : Fire salamanders are conspicuous to potential predators at night. Confirming historical experiments, the background albedo experienced by a larva has a carry‐over effect on its postmetamorphic black‐and‐yellow coloration but not on its toxicity.